Microglial intracellular Ca2+ signaling as a target of antipsychotic actions for the treatment of schizophrenia - Mizoguchi, Yoshito; Kato, Takahiro A.; Horikawa, Hideki; Monji, Akira (Frontiers in Cellular Neuroscience, 2014)
Microglia are resident innate immune cells which release many factors including proinflammatory cytokines, nitric oxide (NO) and neurotrophic factors when they are activated in response to immunological stimuli. Recent reports show that pathophysiology of schizophrenia is related to the inflammatory responses mediated by microglia. Intracellular Ca2+ signaling, which is mainly controlled by the endoplasmic reticulum (ER), is important for microglial functions such as release of NO and cytokines, migration, ramification and deramification. In addition, alteration of intracellular Ca2+ signaling underlies the pathophysiology of schizophrenia, while it remains unclear how typical or atypical antipsychotics affect intracellular Ca2+ mobilization in microglial cells. This mini-review article summarizes recent findings on cellular mechanisms underlying the characteristic differences in the actions of antipsychotics on microglial intracellular Ca2+ signaling and reinforces the importance of the ER of microglial cells as a target of antipsychotics for the treatment of schizophrenia.